Azaphosphatranes as Hydrogen‐Bonding Organocatalysts for the Activation of Carbonyl Groups: Investigation of Lactide Ring‐Opening Polymerization. Issue 8 (18th February 2016) - Zhang, Dawei; Jardel, Damien; Peruch, Frédéric; Calin, Nathalie; Dufaud, Véronique; Dutasta, Jean‐Pierre; Martinez, Alexandre; Bibal, Brigitte
Abstract: The hydrogen‐bonding activation of C=O bonds by azaphosphatranes was explored in a model reaction, i.e., the ring‐opening polymerization of lactide. The polymerization process was controlled, and allowed the preparation of polylactides with narrow dispersity under mild conditions (20 °C, 24 h, 10 mol‐% catalyst loading). Interestingly, the steric hindrance of azaphosphatranes, as globular rigid structures, prevents any undesired interaction with the tertiary amine cocatalysts, as shown by X‐ray analysis and semi‐empirical calculations. In contrast to their organocatalytic activity in the CO2 /epoxide reaction, all of the phosphonium derivatives tested were found to be efficient catalysts in this ROP benchmark reaction. Abstract : Azaphosphatrane phosphonium salts showed catalytic activity for carbonyl activation. This was evaluated using a benchmark transformation, i.e., the ring‐opening polymerization of lactide.